Proposed conception for the program of preparing an Islamic education teacher in the primary stage in light of quality standards and academic accreditation - Aljohani, Awad Zuriban (Journal of Curriculum and Teaching Methodology, 2023)
The current study aims mainly to prepare a proposed conception for the program of preparing an Islamic education teacher in the primary stage in light of quality standards and academic accreditation, and the study followed the descriptive analytical approach. For the proposed program, which are: (objectives- course content- activities, electronic means and teaching methods- evaluation) and many sub-indicators fall under each main axis. In light of the results reached for the list of quality standards and academic accreditation, the researcher hopes that this study will contribute to the advancement of the preparation program and its future aspirations and activate the role of the preparation colleges to keep pace with the rapid and successive developments in order to achieve high quality outputs.